Addressing Inequities in African American Student Achievement: Using Cultural Proficiency and a Dual Capacity Building Framework - Clark-Louque, Angela; Latunde, Yvette C. (Frontiers in Education, 2019)
The amalgamation of race and disability produces a complex set of challenges for school leaders seeking to provide equitable opportunities for African American students and families. Culturally proficient school leaders and their influence in schools is second only to classroom instruction. Although concern is often focused on student achievement, little attention has been given to how schools have fallen into re-segregation practices that lead to gaps in opportunity and achievement for these students.. Realizing that there are steps school leaders can take to address re-segregation practices and inequities, we offer recommendations and strategies for addressing schools’ disproportional segments of special education, discipline, and Gifted and Talented Education (GATE) programs by using culturally proficient leadership and a dual capacity building framework.